'Anything was possible': (In)fidelities, (dis)connections and narcissistic (self-)love in Alice Munro's 'The Bear Came over the Mountain'. Issue 1 (1st April 2019) - Disney, Dan
In one of Alice Munro's longer works of short fiction, 'The Bear Came over the Mountain', readers are thrust into a narrative in which the protagonist, Grant, is forced to place his ageing and forgetful wife Fiona into a residential care facility. So amnesic is Fiona that, no longer remembering she has hitherto existed happily alongside Grant, she soon forms an intimate friendship with another resident, Aubrey. But Grant is no sympathetic protagonist and Munro reveals how, over the decades, he has habitually conducted a series of secretive extramarital affairs, often with the students he teaches at the local university. Reading a range of texts making taxonomical survey of love (including Plato's Symposium, Barthes' A Lover's Discourse and Comte-Sponville's A Short Treatise on the Great Virtues), this article surmises Grant to be dangerously non-empathetic, unwittingly self-parodying and unthinkingly transgressive; within phallogocentric orders, time and again the women surrounding this husband‐teacher‐lecher are shown to be merely instrumental to his gratifications. When Aubrey's wife Marian arrives on the scene, Grant falls immediately into the role of fetishizing, perplexingly ordinary-seeming predator; in his flirtations, his actions can be read as methodically self-impoverishing. Beyond a stylized performance devoid of meaningful content, this is a narcissist with nothing to declare beyond a duplicitous and blind, dizzying, self-justifying internal chaos.